PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI TERBIMBING UNTUK MELATIH LITERASI SAINS SISWA - Sri Sumarti; Yuni Sri Rahayu; Madlazim Madlazim (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research aims to develop guided inquiry based teaching materials which is valid, practical, and effective to facilitate the students scientific literacy. The development of teaching material used the 4D model  and was tested in grade 7th-D of SMP GEMA 45 in the second semester of  2014/2015 by using the Pre-Experimental One-Group Pretest-Posttest Design. The data collection used documentation observation, test, and quetionnaires. The data analysis techniques used quantitative descriptive analysis.The results of this research are:1) Teaching material developed is valid categorised  to be use consisted of Syllabus, Lesson Plan, Student Worksheet, Student Book and Test of student learning outcomes; 2) The practicality of teaching material in terms of a good category in feasibility of lesson plans, the students activities in accordance with  inquiry model and students give a positive responses toward teaching material and implementation of teaching material developed; and 3) The teaching material effectiveness in terms of: (a) Improving students learning achievement seen from the individual and classical completeness; (b) Improving students scientific literacy by getting gain score between middle until high category. Based on data analyzed the teaching materials based on guided inquiry are valid, practical, and effective to facilitate the students scientific literacy. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran berbasis inkuiri terbimbing yang layak (valid, praktis, dan efektif) untuk melatih literasi sains siswa. Pengembangan perangkat pembelajaran menggunakan model 4D  dan diujicobakan di kelas VII-D SMP GEMA 45 semester genap tahun ajaran 2014/2015 dengan One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode dokumentasi, observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif. Hasil penelitian ini menunjukkan,: 1) Perangkat pembelajaran yang dikembangkan berkategori valid; 2) Perangkat pembelajaran berketagori praktis ditinjau dari keterlaksanaan RPP, aktivitas siswa sesuai dengan tahap-tahap model inkuiri, dan siswa merespon positif perangkat yang dikembangkan dan implementasinya; serta 3) Perangkat pembelajaran telah efektif ditinjau dari: (a) Peningkatan pengetahuan siswa (b) Peningkatan literasi sains  siswa. Berdasarkan hasil analisis data dapat disimpulkan bahwa perangkat pembelajaran berbasis  inkuiri terbimbing yang dikembangkan valid, praktis, dan efektif untuk melatih literasi sains siswa sehingga layak untuk digunakan.